Peranan Pembelajaran Al-Qur’an dalam Membentuk Karakter Toleransi di SMKS Muhammadiyah Berau - Ibnu Abbas; Darul Ihsan; Ahmad Yakin; Handoko; Khoiriyah (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2026)
This study aims to analyze the role of Qur’anic learning in shaping students’ tolerance character at SMKS Muhammadiyah Berau. The research employs a qualitative descriptive-analytical approach to explore in depth the processes, meanings, and experiences involved in implementing Qur’anic learning within the framework of Islamic character education. Data were collected through observation, in-depth interviews, and documentation involving school principals, Islamic Education teachers, Qur’anic subject teachers, and students of grades X–XII. Data analysis followed the interactive model of data reduction, data display, and conclusion drawing, supported by triangulation and member checking to ensure validity. The findings indicate that Qur’anic learning contributes significantly to the internalization of tolerance values when conducted contextually, reflectively, and supported by teachers’ exemplary behavior (uswah hasanah). Dialogical approaches, inclusive classroom interactions, and school culture that promotes moderation strengthen students’ attitudes of respect, justice, and social harmony. However, external influences such as social media and environmental factors remain challenges that require adaptive and collaborative educational strategies. This study highlights the importance of integrating faith, knowledge, and moral values in Qur’anic learning to foster inclusive and tolerant student character in Islamic educational institutions.